Penerapan Model Pembelajaran Guided Note Taking (GNT) untuk Meningkatkan Hasil Belajar Biologi Siswa Kelas X IPA SMA Satria Makassar - Astuti, Wiwik Wiji (Universitas Negeri Makassar, 2019)
Abstract. This research is a classroom action research that aims to improve the learning outcomes of class X IPA SMA Satria Makassar through the use of Guided Note Taking (GNT) learning models. The subjects of this study were students of class X IPA SMA Satria Makassar for the odd semester in academic year 2018/2019 which consists of 20 students. The data collection techniques include learning activity data obtained through observation sheets and data on student biology learning outcomes obtained using student biology learning outcomes tests which are then analyzed using descriptive statistics. The results of observations of student learning activities showed generally an increase from cycle I to cycle II in each student learning activity observed. The results of quantitative descriptive statistical analysis of the students' biology learning outcomes indicate that the average student learning outcomes in the first cycle were 54.0% and in the second cycle were 78.7%. so that the percentage obtained increase in student biology learning outcomesÂ by 24.7%. Keywords: gnt learning model, learning outcomes